Transforming Mathematics Learning through Storytelling and Digital Comic Models in Explaining Elementary School Students' Problem-Solving Abilities - Azarine Shufaira Mulya Rahman; Rusnilawati Rusnilawati (Papanda Publisher, 2026)
Mathematical problem-solving ability remains critically underdeveloped among elementary school students, largely due to the dominance of conventional, media-poor instruction that fails to make abstract concepts contextually accessible. This study examined the effectiveness of a storytelling learning model supported by digital comic media in improving the mathematical problem-solving ability of fourth-grade students. A quasi-experimental design with a Nonequivalent Control Group was employed involving 54 students (27 experimental, 27 control) at an elementary school in Klaten Regency, Central Java, Indonesia. Data were collected through pre-test and post-test essay instruments aligned with Polya's four-stage problem-solving framework (validity r > 0.381; Cronbach's α = 0.984) and analyzed using independent t-tests, dependent t-tests, and the Normalized Gain (N-Gain) index. The experimental group achieved a post-test mean of 84.9 and an N-Gain of 0.89 (high category), compared to 71.1 and 0.38 (moderate) in the control group, with a statistically significant between-group difference (p = 0.001). These findings demonstrate that the purposeful integration of narrative-based pedagogy and multimodal digital media, grounded in Dual Coding Theory and constructivist principles, creates a learning environment that substantially outperforms conventional instruction in fostering structured, meaningful mathematical problem-solving at the elementary level.